Preliminary checklist of vascular plants of Bioko Island (Equatorial Guinea) - Velayos, Mauricio; Cabezas, Francisco; Barberá, Patricia; de la Estrella, Manuel; Aedo, Carlos; Morales, Ramón; Quintanar, Alejandro; Velayos, Guillermo; Fero, Maximiliano (Botanica Complutensis, 2013)
We present a list of taxa of vascular plants growing on Bioko (Equatorial Guinea). We are aware that there are still many unexplored areas,so it should be consider just as a first draft list. It is based on both herbarium specimens and on bibliographic references. The complete data, supportingeach record, can be consulted in our online database at http://www.floradeguinea.com/herbario/. To the moment, there are known 2029taxa from the island.
Keywords: biodiversity; Gulf of Guinea Islands; Equatorial Guinea; Bioko; floristic